PENGARUH MEDIA PEMBELAJARAN YANG DIGUNAKAN GURU TERHADAP HASIL BELAJAR SISWA DI SMA NEGERI 10 PEKANBARU - Rahmadani, Rezky; Trisnawati, Fenny; ', Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : Education, in the process requires the learning media that is able to create conditions better learning so as to create a sense of fun and curiosity in students to achieve a goal of learning in the form of learning outcomes. This study is a class action (Classroom Action Research (CAR)). This research was done in class X SMA 10 Pekanbaru in the second semester of FY 2016/2017. Its object is the use of media in the learning process. Results from the study showed that the use of instructional media on the subjects of Economic improve learning outcomes of value - average test cycle I 68.54 into 80.08 in value - average test cycle II class with learning completeness reached 89.58% higher from the default of 78.Key word : Instructional Media, learning outcomes